Transceiver optimization for AF MIMO relay systems with wireless powered relay nodes - Li, Bin; Rong, Yue (2017)
© 2017 University of Western Australia. In this paper, we study a two-hop amplify-and-forward (AF) multiple-input multiple-output (MIMO) relay system, where the relay node has no self-power supply, and relies on harvesting the radio frequency energy transferred from the source node to forward information from source to destination. We apply the time switching (TS) protocol between wireless information and energy transfer. As a novel contribution of this paper, we propose a more general energy consumption constraint at the source node during the information and energy transfer, which includes the constant power constraints used in existing works as special cases. We study the joint optimization of the source precoding matrices, the relay amplifying matrix, and the TS factor to maximize the source-destination mutual information (MI). The optimal structure of the source and relay matrices is derived, which reduces the original transceiver optimization problem to a simpler power allocation problem. Numerical simulations show that the proposed algorithm yield higher system MI and better rate-energy tradeoff than an existing approach.